EFFECTS OF CONFLICT OF INTEREST ON PROCUREMENT PERFORMANCE IN REFERRAL HOSPITALS IN KENYA: A CASE OF KENYATTA NATIONAL HOSPITAL (KNH) NAIROBI, KENYA - Philly, Ruttoh Kiprono; Were, Dr. Susan; Nkirina, Dr.Severina P. (International Journal of Supply Chain Management, 2017)
Purpose: The study aimed at evaluating the effect of conflict of interest on procurement performance in Referral Hospitals in Kenya. Materials and methods: Descriptive research design was used for the study and the questionnaire was the main data collection instrument, Slovin's formula was used to pick a sample of 131 respondents from a target population of 194 staff working in supply chain department at KNH. Both quantitative and qualitative methods of data analysis were used to analyse the gathered data. The quantitative data generated was analysed by use of descriptive statistics feature in SPSS to generate information which was presented using tables, charts, frequency distribution table and percentages and inferential statistics to make predictions or inferences about the population from observations and analyses of sample. The regression model was used to show the relationship between the dependent variable and the independent variables. A sample size of 131 respondents was targeted for this study, with 117 respondents returning fully filled questionnaires. Results: The study established the influence of conflict of interest on procurement performance in Kenyatta National Hospital and it can be summarized to consider first, the interest of one's organization in all transactions and to carry out procurement process effectively and believe in its established policies. Recommendations: The study recommends that legal intervention in protecting public institutions against inappropriate and unethical practices in the procurement operations including fraudulent suppliers activities , organization should be emphasizing on performance measurement and laying down proper checks for all contracts, setting supplier selection structures that avoid political interference and augmenting of accountability management practices to ensure supplier and public institutions work towards the same goal and for the interest of the public .